Effects of Occupational Health and Safety on Healthy Lifestyle Behaviors of Workers Employed in a Private Company in Turkey - Nilgun Ulutasdemir; Meryem Kilic; Özge Zeki; Fatma Begendi (Ubiquity Press, 2015)
Background: It has been suggested that inappropriate working conditions and unsafe environments at construction sites, longer working hours, and inadequate workplaces adversely affect the health behaviors of workers. Objective: The aim of this study was to evaluate the effect of occupational health and safety (OHS) practices on healthy lifestyle behaviors of workers employed at a construction site of a private company in Gaziantep, Turkey. Methods: The sampling size of this descriptive study consisted of 400 employees working at the construction site between December 2014 and January 2015. In all, 341 employees still working or participating in the study during the period of this questionnaire study were included in the sampling. Data from the survey were derived from responses to questions regarding sociodemographic characteristics, OHS applications, health state, and working conditions, as well as to the questions in on the Healthy Lifestyle Behaviors Scale (HLBS), under direct surveillance. Findings: Male workers with a mean age of 30.61 ± 8.68 years constituted the study population. Of the workers, 41.9% had a primary school education. The majority received professional and OHS training (65.7% and 79.2%, respectively). Although 83.9% reported using personal protective equipment (PPE), only 2.1% said they had experienced an occupational accident. Total mean score of HLBS scale was 116.91 ± 25.62 points. Workers who had positive thoughts about their jobs demonstrated healthy lifestyle behaviors ('P' = .0001). A positive direct correlation was detected between the training the workers received and the use of PPE ('P' = .0001). In all, 38.1% of the workers reported experiencing work stress at the time of the study. Mean HLBS scores of those experiencing work stress were lower than the scores for workers not experiencing stress ('P' < .05). Conclusion: Receiving OHS and professional training and using of PPE favorably affect healthy lifestyle behaviors.